(untitled) (Bangladesh Journal of Medical Education, 2014)
This descriptive type of cross sectional study was carried out to find out the causes of dropouts and repeated failures (defaulters) of medical students in Bangladesh. The study was carried out in seven (Three government and four Nongovernment) medical colleges in Bangladesh over a period from July 2011 to June 2012. All dropout and defaulter students were the study population. A total of 59 respondents were interviewed, out of them 11 respondents were dropouts and 48 were defaulters. Convenience sampling technique was adopted and data was collected by the researcher himself. Data was collected from those who got admitted in medical college in the year 2003 and thereafter. So, medial students of different level and intern doctors, who were agreed, were enrolled for collection of data by face to face in depth interview. Study revealed that the most important reasons for dropouts and defaulters were lacking of personal interest and less capability for understanding the medical subjects, non-friendly and non-cooperative attitude of teachers; content overloaded curriculum and threatening environment of oral examinations; personal illness and illness of family members; poor institutional set up; lack of facilities for counseling and remedial actions. Among the respondents it was also found that the male and the higher economic class students were more dropped out or became defaulters in the professional examinations. Study also revealed some valuable suggestions to avoid occurrences of dropouts and defaulters. Suggestions were strict regularity, sincerity and attention should be paid to all types of classes including lectures, clinical, tutorial and practical; personal interest and ability should be given highest importance in case of medical admission. They also emphasized on the revision of medical curriculum where the needs of the students would be reflected and the curriculum should be more appropriate and practical oriented. A coordinated class, tutorials and examination system should be developed in each medical college, so that all students can prepare themselves for examination properly. They also suggested that teachers and examiners at all levels should be friendly and cooperative, and should pay special attention to the poor performing students to overcome their weaknesses. They also suggested that study in partnership should be encouraged and there should be adequate hostel arrangement with proper food and recreation facilities. The respondents also suggested for provision of counseling facilities and make-up classes for academically weak students. They further suggested that special sympathy and support should be provided to those who are ill or who are sufferer for the illness of parents or any other family members. Further analytic studies with representative samples should be conducted which will include students with acceptable level of performance (students who pass regularly and if failure, not more than once during whole MBBS course) as well as students whose performance below acceptable level (defaulters and dropouts). This type of study will help to determine the reasons of defaulters and dropouts. So the appropriate strategy can be adopted to avoid dropouts and defaulters. DOI: http://dx.doi.org/10.3329/bjme.v2i2.18134 Bangladesh Journal of Medical Education Vol.2(2) 2011: 1-6